Effect of a phase transition on the binding of 1-anilino-8-naphthalenesulfonate to phospholipid membranes. - Jacobson, K (1976)
The binding of 1-anilino-8-naphthalenesulfonate (ANS) to dipalmitoyl-phosphatidycholine (DPPC)-sonicated vesicles was measured by a fluorimetric method in the vicinity of the gel-to-liquid crystalline phase transition temperature (Tm). A similar measurement was performed on large multimellar DPPC vesicles through equilibrium dialysis. Both measurements demonstrated anomalous dye binding in the temperature region of the Tm and slightly above (prefreezing region). The amount of ANS bound at this temperature region was in excess of what would be expected based on extrapolation of the high temperature binding data; just below the Tm, the amount of bound dye decreased abruptly. The fluorimetric studies on vesicles also indicated that inner monolayer binding of ANS was markedly inhibited below the Tm. The possibility that the increase in bound dye in the prefreezing region was caused by enhanced lateral compressibility, density fluctuations, or additional binding sites at the boundary of transient gel-like clusters is discussed and the general topic of anomalous increases in various membrane processes in the vicinity of a phase transition is briefly reviewed.